SOSIALISASI BAGI IBU RUMAH TANGGA â€œEKONOMI DAN BISNIS DALAM PANDANGAN ISLAMâ€ - Harahap, Ludwina; Dwiningsih, Nurhidayati; Efendri, Efendri (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
This community service activity aims to discuss Economics and Business from an Islamic perspective for housewives who are in business. The material provided included the basic principles of Islamic economics that can be applied, and how they can take advantage of economic potential while still adhering to Sharia values. Thus, housewives can play an active role in building the family economy and society without neglecting their main obligations and responsibilities in the household. The service was implemented at the Green Cileungsi Housing, Cileungsi, Bogor. Through this service, it is hoped that the understanding of Economics and business under Islamic law for housewives who carry out business or entrepreneurial activities can increase so that it does not contradict Islamic teachings. Service activities are carried out through material presentations, discussions, and questions and answers so that material provision runs more effectively. It is hoped that this activity will have a positive impact on all involved, starting from the implementers, supervisors, and all parties involved